If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 3 = 14s Reorder the terms: 3 + 2s = 14s Solving 3 + 2s = 14s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-14s' to each side of the equation. 3 + 2s + -14s = 14s + -14s Combine like terms: 2s + -14s = -12s 3 + -12s = 14s + -14s Combine like terms: 14s + -14s = 0 3 + -12s = 0 Add '-3' to each side of the equation. 3 + -3 + -12s = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -12s = 0 + -3 -12s = 0 + -3 Combine like terms: 0 + -3 = -3 -12s = -3 Divide each side by '-12'. s = 0.25 Simplifying s = 0.25
| x=(x-2)*(2*x+4) | | 4x+8y=16 | | 7x+3=2x-4 | | 4x+1=6x-7 | | 2x+8-15=45 | | 2x+8-25=45 | | 2(4n+8)= | | (5)10-(5)13= | | -6x=80 | | a-z=-5(39-a)-3 | | 171-3x=24x+18 | | x^2-16x+64=3 | | x=2*x-4 | | x^2+2x+1=49 | | y=30+11y | | 3x+2b=x+8 | | x=x-2*2x-4 | | 9x^2-14x-8=0 | | x^2+20x-3=0 | | 56753366x=786556 | | 9x^2+65x+14=0 | | a=12a-44 | | x=(x-2)*(2x-4) | | 5x^2+38x+21=0 | | x^2+18x+90=0 | | x^2+18+90=0 | | 20x+35=0 | | 6x+20=3x+11 | | x=x-2*(4) | | x=4*(x-2) | | x=2*x+1-(2*2+1) | | (x-7)(2x+9)=0 |